2017
DOI: 10.1016/j.cjtee.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Return to work after trauma: A survival analysis

Abstract: PurposeTo evaluate the return to work (RTW) rate, time and predictors among trauma patients using survival analysis.MethodsThis cohort study was conducted with a three-month follow-up on 300 trauma patients hospitalized in Shahid Beheshti Hospital, Kashan, Iran in 2014. The data were collected through conducting interviews and referring to patients' medical records during their hospital stay and follow-up information at one & three months after discharge from hospital. Final analysis was conducted on the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
2
18
2
Order By: Relevance
“…The proportion of RTW in our study is higher compared to previous studies [44,45]. This could be explained by differences in characteristics of the studies; e.g.…”
Section: Rtwcontrasting
confidence: 85%
See 1 more Smart Citation
“…The proportion of RTW in our study is higher compared to previous studies [44,45]. This could be explained by differences in characteristics of the studies; e.g.…”
Section: Rtwcontrasting
confidence: 85%
“…This could be explained by differences in characteristics of the studies; e.g. the injury severity in our study was lower [44] or differences in definition of RTW [45]. Our study showed that the probability of RTW decreased over time, but did not stabilize up to 24 months after injury.…”
Section: Rtwcontrasting
confidence: 54%
“…It is the major cause of mortality, disability and morbidity among reproductive age group populations in the developing countries and in the world [2,3]. Trauma also contributes to about 10% of disease burden worldwide [4]. Among African nations the rate of injury mortality in 2004 was the highest in Nigeria followed by South Africa and Ethiopia as the second and third, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the group of patients who did return to their place of work after trauma, most of them had the length of hospital stay of 1-6 days. In the other group, hospital stay of more than 6 days prevailed 28 .…”
Section: Epo = Erythropoietinmentioning
confidence: 94%